VIOLENCE AGAINST STREET CHILDREN (A Study On Violence Against Street Girls In Pekanbaru) - Putri, Elsa Ade; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
One of the consequences of the prolonged economic crisis is the increase number of street children. There are a great number of street children can be found in a small town as like Pekan Baru. An increase number of street children are not only full of street boys, street girls also begin to pack the center of city such as crossroads, traffic lights, markets and other places. This research analyzes the violence experienced by street girls. There are five violated street girls interviewed as the informants. This research aims to know what the street children’s daily activities are, what kinds of violence experienced by street girls, and the reasons why they still stand working on street. This research uses qualitative approach. In seeking the data, the researcher uses observation, interview, and documentation as method of study. Selection of informants is done by using purposive sampling. There are five street children from different location in Pekan Baru that are being interviewed to do this research. the researcher concludes that the street girls often experience vary violence they are: 1) physical violence 2) psychological violence 3) sexual abuse and 4) social violence. This research finds the culprits of that violence usually are friends, gangsters, police officers and street children’s own parents. The violence cases they have experienced do not come to the authorities because they will deal with the case in their own way.Keywords: street children, street girls, violence